2014
DOI: 10.1186/1471-244x-14-92
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oxytocin administration early after psychotrauma in preventing the development of PTSD: study protocol of a randomized controlled trial

Abstract: BackgroundCurrently few evidence based interventions are available for the prevention of PTSD within the first weeks after trauma. Increased risk for PTSD development is associated with dysregulated fear and stress responses prior to and shortly after trauma, as well as with a lack of perceived social support early after trauma. Oxytocin is a potent regulator of these processes. Therefore, we propose that oxytocin may be important in reducing adverse consequences of trauma. The ‘BONDS’ study is conducted in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 101 publications
0
36
3
2
Order By: Relevance
“…Given that Paloyelis et al observed neural OT effects peaked between 39 and 51 min post administration and slowly attenuated onwards (Paloyelis et al, 2014), we explored correlations of duration between intranasal administration, scanning, and our observed neural effects in the OT group (see Supplementary Material). Participants who also enrolled in the randomized clinical trial on the efficacy of multiple OT intranasal doses for PTSD prevention (n = 23) (Frijling et al, 2014) were scanned after the first intranasal dose.…”
Section: Design and Experimental Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that Paloyelis et al observed neural OT effects peaked between 39 and 51 min post administration and slowly attenuated onwards (Paloyelis et al, 2014), we explored correlations of duration between intranasal administration, scanning, and our observed neural effects in the OT group (see Supplementary Material). Participants who also enrolled in the randomized clinical trial on the efficacy of multiple OT intranasal doses for PTSD prevention (n = 23) (Frijling et al, 2014) were scanned after the first intranasal dose.…”
Section: Design and Experimental Interventionmentioning
confidence: 99%
“…Acute distress was assessed using the Trauma Screening Questionnaire (TSQ; cutoff score ⩾ 5 (Mouthaan et al, 2014;Walters et al, 2007) and Peritraumatic Distress Inventory (PDI; cutoff score ⩾ 17 (Nishi et al, 2010) (see Frijling et al (2014) for details). Individuals with increased PTSD risk (ie, scoring above TSQ and/or PDI cutoff) were invited to participate.…”
Section: Procedure-screening and Baseline Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Intranasal oxytocin is also being studied for the prevention of posttraumatic stress disorder in persons who experience trauma. 30 …”
Section: Intranasal Oxytocinmentioning
confidence: 99%
“…Possible investigation targets for future research include cannabinoid compounds, and especially cannabidiol (CBD), since this compound seems to play an important role in the blockade of the reconsolidation of aversive memories 41 . In addition, preclinical studies provide support for the test of oxytocin as a promising strategy in the prevention of PTSD-like manifestations 42 .…”
Section: Resultsmentioning
confidence: 99%